Statistical Models for Mobile Telephony Growth in Oman - M.I., Ahmad; ., Almamri A. (Information Management and Business Review, 2014)
This study examines the growth of mobile telephony in Oman and investigates the determinants of this growth. The growth rates were estimated by fitting four statistical models namely, Logistic, Gompertz, Exponential and Autoregressive to fifteen years of data on annual numbers of mobile subscribers. The in-sample and out-of-sample forecasting performance of these models was assessed by Mean Absolute Deviation (MAD) and Mean Square Error measures. Based on this criterion it was observed that the Gompertz model outperformed the other models under consideration and gave the minimum forecast error. This model was then used to estimate the speed of diffusion which was regressed on potential factors that could affect the growth of mobile telephony. The factors considered were fixed line service, prepaid service, per capita income, consumer price index and the number of operators. All these factors were found to have significant effect on the speed of diffusion of the mobile telephony in Oman.